A novel sandwich structured phase change material with well impact energy absorption performance for Li-ion battery application. (August 2021) - Zhang, Yafang; Huang, Juhua; Cao, Ming; Du, Guoping; Liu, Ziqiang; wang, Li
Highlights: A novel energy absorption and Anti-collision phase change material is proposed. The EG/PW/Al-f has high thermal conductivity and well thermal stability. The EG/PW/Al-f exhibits good thermal management performance. The FE model was developed to investigate the Anti-collision performance of EG/PW/Al-f. Abstract: Thermal runaway in battery induced by rapid charging/discharging process and collision due to car accident are the two major safety issues. Therefore, we designed phase change materials (PCM) with collision energy absorption properties. The paraffin wax (PW) was mixed with expanded graphite (EG) to obtain an EG/PW composite material. After that, the EG/PW powder was pressed into the foamed aluminum (Al-f) hole to obtain an EG/PW/ Al-f sandwich structured PCM. The EG/PW/Al-f PCM was applied to a battery for thermal management and collision performance research. The results show that when the PCM was attached to the battery and the discharge is kept constant at 1 C/1.5 C (capacity) discharge rate, the battery temperature dramatically decreased; moreover, its temperature difference was more uniform than it was in the absence of PCM. Particularly, the EG/PW/Al-f PCM showed good impact energy absorption performance. The results of the impact experiment showed that when the battery suffered from a high-speed steel ball impact, the EG/PW/Al-f PCM attached to the surface of the battery could protect the battery well without any internal short circuit. Furthermore, the finite element model was developed to analyze the impact process of the battery. The results of the numerical solution match well with the experimental results; the experiment measured the indentation depth of a battery due to the steel ball falling from 2 m height. The results provide a new way to design PCM with both impact energy and heat absorption properties for battery application.